PENGARUH INTERPERSONAL INFLUENCE, ALTRUISM, DAN ENVIRONMENT KNOWLEDGE TERHADAP GREEN PURCHASING BEHAVIOUR KONSUMEN THE BODY SHOP YANG DIMEDIASI OLEH ENVIRONMENT ATTITUDE - Yokie Radnan Kristiyono; Caroline Felim (Ultima Management : Jurnal Ilmu Manajemen, 2021)
Abstract-This research was conducted to determine the relationship between interpersonal influence, altruism, environmental knowledge and green purchasing behaviour mediated by environmental attitudes towards consumers of The Body Shop in the Jakarta, Tangerang, Depok, Bekasi and Bogor areas. This research will focus on consumers of The Body Shop where the researchers conducted this research because the awareness of young consumers towards environmentally friendly products is still low. This research was conducted using a quantitative approach. The data used in this study were collected through an instrument in the form of an electronic questionnaire, namely Google Form that was spread on social media. The findings of this research show that interpersonal influence has a positive and significant effect on environment attitude; altruism has a positive effect on environment attitude; environment knowledge has no positive effect on environment attitude; and environment attitude has a positive effect on green purchasing behaviour. The managerial implication that can be given from this research is that marketers can increase consumer knowledge of the environment so that it can encourage consumers to pay attention to their attitudes towards the environment and can lead to consumer buying behaviour for environmentally friendly products. Keywords: Interpersonal Influence; Altruism; Environment Knowledge; Green Purchasing Behavior; Environment Attitude